Médecine Vétérinaire et santé publique : les Campylobacters^) Isolement des Campylobacters et recherche de C. coli à partir du colon du porc à Lubumbashi (Zaïre) - Mathieu, AM. (Tropicultura, 1986)
Veterinary medicine and public health Campylobacters. This study concerns the isolation Campylobacters and the research of C. coli from the colon contents in 60 normal slaughtered pigs in Lubumbashi (Zaire) ; 53 among them (88, 3 %) have been recorded as Campylobacters carriers. Over 22 isolated strains, 13 have been identified as Campylobacters coli.